En säregen styrka - Didong , Paola (Tidskrift för genusvetenskap, 1997)
The article is an attempt to describe the actress Stina Ekb1ads's artistry in the role of Renée in Madame de Sade by Yukio Mishima. The play was produced at the Royal Dramatic Theatre in Stockholm 1989. In her appearance on stage Stina Ekblad gives the impression of considerable strength and at the same time of great frailty. These features seem to be intimately connected. They exist in the fictious character of the play and are also integral parts of Ekblad's personality. A particular shimmer is revealed as they coalesce. In Ekblad's acting there is also a point of resistance against "the male gaze". When she occasionally turns on a traditional womanly submissive charm it becomes part of a strategy towards her companions and adversaries on stage. As il becomes a performative gesture she manages to keep a subject position. The same thing is true for her gestures connected to the rich poetical imagery in the text. Interpreting strong poetical texts can be regarded as a speciality for Ekblad. By letting her movements follow the images she extends the part and slips out of the mimetic trap of depicting a fictious woman taken to be real and nothing else. Ekblad takes command by making extensive use of the male naming privilege the role of Renée offers. Through her interpretation the character is never victimized, in spite of her sufferings.